Blood pressure lowering effects of a novel isometric exercise device following a 4-week isometric handgrip intervention - Baddeley-White DS; McGowan CL; Howden R; Gordon BDH; Kyberd P; Swaine IL (Dove Medical Press, 2019)
Daniel S Baddeley-White,1 Cheri L McGowan,2 Reuben Howden,3 Benjamin DH Gordon,4 Peter Kyberd,5 Ian L Swaine1,21Department of Life & Sport Sciences, University of Greenwich, Medway Campus, London, UK; 2Department of Kinesiology, Faculty of Human Kinetics, University of Windsor, Windsor, ON, Canada; 3Department of Kinesiology, University of North Carolina at Charlotte, Charlotte, NC, USA; 4Department of Exercise and Rehabilitative Sciences, Slippery Rock University, Slippery Rock, PA, USA; 5Department of Engineering Science, University of Greenwich, Medway Campus, London, UKBackground: Hypertension is the leading risk factor for global mortality. Isometric resistance exercise training reduces blood pressure (BP). However, the protocols used are often limited by cost/immobility and the use of rigid exercise modalities. In response, a novel more versatile, isometric exercise (IE) device, the IsoBall (IB) was created.Purpose: The aim of this study was to test the BP-lowering effectiveness of this prototype.Methods: Twenty-three healthy participants (29.10±2.19 years old, 173.95±3.83 cm, 75.43±5.06 kg, SBP 127.10±10.37 mmHg, DBP 70.40±6.77 mmHg) were randomly allocated to either a control group (CON) or 2 isometric handgrip (IHG) training groups that used the Zona plus (ZON) and IB devices. The intervention groups completed 3 sessions each week of 4, 2 min IHG at 30% maximal voluntary contraction, with a 1-min rest, for 4 weeks. Resting BP, heart rate (HR) and IHG strength were measured in all groups at baseline and postintervention.Results: Postintervention systolic BP (SBP) was significantly lower in both ZON (114.5±8.2 mmHg, p = 0.000) and IB (119.9±7.0 mmHg, p = 0.000) compared to control (131.0±12.4 mmHg). Postintervention diastolic BP (DBP) was reduced in both intervention groups (ZON 66.6±7.4 mmHg, p = 0.004; IB 65.7±10.0 mmHg, p = 0.012) compared to CON (71.1±8.8 mmHg). Mean arterial pressure (MAP) was reduced in both groups (ZON 82.6±6.8 mmHg, p = 0.000; IB 84.3±9.1 mmHg, p = 0.000) compared to control (91.0±9.7 mmHg). No significant changes were seen in HR or strength (p > 0.05).Conclusion: The results of this study indicate that both the ZON and IB devices elicit significant SBP, DBP and MAP reductions. Despite the ZON group having larger reductions in BP, no significant differences were found between the two devices. Thus, this study indicates the IB device to be an effective alternative to the ZON that can also be used to perform other IE modalities.Keywords: hypertension, antihypertensive intervention, isometric exercise ball, IsoBall, Zona plus device